Best Practices on the Move: Building Web Apps for Mobile Devices. - NICOLAOU, ALEX (Communications of the ACM, 2013)
The article discusses the construction of web applications for mobile devices, focusing on best practices for website performance optimization as of August 2013. Recommendations include minimizing HTTP requests, using compression on content that is not an image or a video, preloading components, and managing caches. Topics include website design, software applications, the JavaScript computer program language, cascading style sheets (CSS), and the potential differences between desktop and mobile design.